Analysis of the Employed Manpower in the Ecuadorian Agricultural Sector - Barreno Benavides, Luis (2011)
The agricultural sector plays a fundamental role in a country's economy, not only because of its function as a supplier of food and raw materials for domestic consumption, as well as export products, but also because of its ability to generate employment. This document analyzes the workforce employed in this sector, from different perspectives, population groups and percentages of contribution to the national economy in order to consider the future of this group and what implications low income levels have. of those who work in this sector.